Positive electrode lithium supplement composite material, lithium ion battery and preparation method of lithium ion battery
By using composite materials such as lithium peroxide and amorphous carbon cladding in lithium-ion batteries, the problem of loss of active lithium during the first charging and discharging of lithium-ion batteries is solved, the battery conductivity and energy density are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202510709329.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-29
AI Technical Summary
The existing lithium-ion batteries permanently consume active lithium due to the formation of SEI film during the first charging and discharging process, resulting in low efficiency for the first time. The existing lithium supplement additives have poor conductivity and high-temperature decomposition and are not applicable, which limits the increase in energy density.
A composite material with a lithium-enhancing material body such as lithium peroxide and lithium oxalate and an amorphous carbon cladding layer is used to form a conductive network through mixing and heat treatment of low-temperature carbon sources to optimize the conductivity and structural stability of the material.
It improves the conductivity and first-time Coulomb efficiency of lithium-ion batteries, reduces the decomposition voltage, increases the lithium supplement capacity, avoids the problem of high-temperature decomposition, and improves the energy density and cycle life of the battery.
Smart Images

Figure CN120565863A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode lithium-supplementing composite material, a lithium-ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used in various fields of society. The transformation of energy structures in the fields of power, consumption, energy storage, etc. has also put forward higher requirements and challenges for the energy density and cycle life of lithium-ion batteries. A key issue that limits the improvement of energy density is that during the first charge and discharge process of lithium-ion batteries, the negative electrode surface will be accompanied by irreversible decomposition of the solvent and lithium salt in the electrolyte, forming a corresponding solid electrolyte interface (SEI) film, which permanently consumes the active lithium inside the battery, resulting in a low first coulombic efficiency (ICE) of the lithium-ion battery, showing a decrease in capacity and energy density. To address this problem, existing technologies usually compensate for the loss of active lithium during the first charge and discharge process by pre-placing an additional lithium source in the battery, thereby achieving a corresponding increase in capacity and energy.
[0003] For example, in the existing lithium replenishment strategy, positive electrode lithium replenishment additives (i.e., positive electrode lithium replenishment composite materials) are generally added during the mixing process of the positive electrode slurry. Due to their advantages such as simple operation, air stability and safety, they have more application prospects. Existing lithium replenishment additives can be roughly divided into binary lithium compounds (such as Li2O, Li2O2, Li2S, Li3N, LiF, etc.), binary lithium compound doping modification (such as Li2O / Co, Li2S / Ni, etc.), ternary lithium compounds (such as Li5FeO4, Li2NiO2, etc.), and organic lithium salts (such as CH3COOLi, Li2C2O4, etc.) according to the type of lithium source. However, due to the poor conductivity of Li2O, Li2O2, Li2C2O4, and Li2CO3, the decomposition potential is too high. Therefore, modification of their conductivity is more conducive to their actual large-scale application.
[0004] In addition, in the existing material preparation process, conductive carbon coating is usually used to achieve the construction of a hierarchical conductive network of the material, optimize the conductive properties of the material, and the effect is better than the physical mixing of the material and conductive carbon. Referring to the existing in-situ carbon coating method, different carbon sources (such as glucose, sucrose, polydopamine, etc.) can be mixed with the material, and the carbon source can be decomposed by heating to achieve in-situ carbon coating on the surface of the material. However, the actual decomposition temperature of existing carbon sources is relatively high, usually above 600-800°C, and some lithium supplements have a low decomposition temperature due to their own physical and chemical properties (such as Li2O2 around 300°C, Li2C2O4 around 400°C), so they are not suitable for this method. Summary of the Invention
[0005] The purpose of the present invention is to provide a positive electrode lithium-supplementing composite material, a lithium-ion battery and a preparation method thereof, which can increase conductivity and reduce decomposition voltage.
[0006] In order to solve the above technical problems, the present invention provides a positive electrode lithium-supplementing composite material, comprising a lithium-supplementing material body and a coating layer; the coating layer covers the surface of the lithium-supplementing material body.
[0007] Furthermore, the lithium-supplementing material in the lithium-supplementing material body includes one or more combinations of lithium peroxide, lithium oxalate, and lithium carbonate.
[0008] Furthermore, the particle size of the main body of the lithium supplement material ranges from 0.5 to 10 μm; the main component of the coating layer includes amorphous carbon; the thickness of the coating layer ranges from 50 to 500 nm; the mass proportion of the main body of the lithium supplement material ranges from 80 to 99%, and the mass proportion of the coating layer ranges from 1 to 20%.
[0009] In addition, the present invention also provides a method for preparing a positive electrode lithium-supplementing composite material. The method for preparing the positive electrode lithium-supplementing composite material as described above specifically includes the following steps:
[0010] mixing the lithium supplement material with a carbon source to obtain a precursor;
[0011] The precursor is subjected to heat treatment to obtain the positive electrode lithium supplement composite material.
[0012] Furthermore, the carbon source includes one or more combinations of carboxymethyl cellulose, polyvinyl pyrrolidone and glycerol.
[0013] Furthermore, the lithium supplement material and the carbon source are mixed to obtain a precursor, which specifically includes: adding the lithium supplement material and the carbon source into a container according to a specified mass ratio, adding a solvent to adjust the solid content, mixing evenly and drying to obtain the precursor.
[0014] Furthermore, the solvent component includes water and / or ethanol; and the solid content ranges from 40% to 80%.
[0015] Furthermore, the heat treatment of the precursor specifically includes: taking the precursor, placing it in a container, and sintering it in a specified gas atmosphere and at a specified temperature for a specified time.
[0016] Furthermore, the specified gas atmosphere includes nitrogen, oxygen or argon; the specified temperature ranges from 100-500° C.; and the specified time ranges from 10-720 min.
[0017] In addition, the present invention also provides a lithium-ion battery, which is made of the positive electrode lithium-replenishing composite material as described above, or made of the positive electrode lithium-replenishing composite material made by the preparation method of the positive electrode lithium-replenishing composite material as described above.
[0018] In addition, the present invention also provides a method for preparing a lithium-ion battery, using the positive electrode lithium-supplementing composite material as described above, or including the method for preparing the positive electrode lithium-supplementing composite material as described above, specifically comprising the following:
[0019] mixing the active material with the positive electrode lithium-supplementing composite material to obtain a mixture;
[0020] adjusting the viscosity and solid content of the mixture;
[0021] coating the mixture on a conductive substrate to form a positive electrode sheet;
[0022] The positive electrode sheet and the negative electrode sheet are processed to obtain a battery.
[0023] Furthermore, the active material includes lithium iron phosphate.
[0024] Through the above technical solution, the present invention has the following beneficial effects:
[0025] The positive-electrode lithium-replenishing composite material produced by this method not only increases conductivity and reduces decomposition voltage compared to existing lithium-replenishing additives and relatively pure lithium-replenishing additives, but also increases lithium-replenishing capacity. Furthermore, the positive-electrode lithium-replenishing composite material produced by this method has a lower proportion of conductive carbon and is physically blended, resulting in improved conductivity optimization. Furthermore, this method does not involve decomposing the carbon source at high temperatures, avoiding the problem of material temperature mismatch, thereby enabling in-situ surface carbon coating of the main lithium-replenishing material at lower temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the overall structure of the positive electrode lithium-supplementing composite material in one embodiment of the present invention;
[0027] Figure 2 This is a flow chart of a method for preparing a positive electrode lithium-supplementing composite material according to one embodiment of the present invention;
[0028] Figure 3 Schematic diagram of the microscopic morphology characterization structure of the positive electrode lithium-supplementing composite material and the initial material in Example 1 of the present invention;
[0029] Figure 4 Schematic diagram of the microscopic morphology characterization structure of the positive electrode lithium-supplementing composite material and the initial material in Reference Example 1 of the present invention.
[0030] In the figure, 1. Main body of lithium-supplementing material; 2. Coating layer. DETAILED DESCRIPTION
[0031] The following, in conjunction with the accompanying drawings, provides a more detailed description of a positive-electrode lithium-supplementing composite material, a lithium-ion battery, and a method for preparing the same, illustrating preferred embodiments of the present invention. It should be understood that those skilled in the art may modify the present invention described herein while still achieving the beneficial effects of the present invention. Therefore, the following description should be understood as generally known to those skilled in the art and is not intended to limit the present invention.
[0032] The following paragraphs describe the present invention in more detail by way of example with reference to the accompanying drawings. The advantages and features of the present invention will become more apparent from the following description. It should be noted that the drawings are greatly simplified and not to exact scale, and are provided solely for the purpose of assisting in the description of the embodiments of the present invention.
[0033] like Figure 1 As shown, an embodiment of the present invention provides a positive electrode lithium-supplementing composite material, comprising a lithium-supplementing material body 1 and a coating layer 2 ; the coating layer 2 covers the surface of the lithium-supplementing material body 1 .
[0034] As a preferred embodiment, the lithium-supplementing material in the lithium-supplementing material body 1 includes one or more combinations of lithium peroxide, lithium oxalate, and lithium carbonate. Preferably, the particle size of the lithium-supplementing material body 1 ranges from 0.5 to 10 μm. For example, 0.5 μm, 2 μm, 4 μm, 6 μm, 8 μm, and 10 μm. Those skilled in the art will appreciate that the particle size of the lithium-supplementing material body 1 can be adjusted based on actual conditions.
[0035] By using a combination of one or more of the above-mentioned lithium-supplementing materials, the conductivity of the material can be improved, which helps to improve the charge and discharge efficiency of the lithium-ion battery.
[0036] As a preferred embodiment, the main component of the coating layer 2 includes amorphous carbon. Amorphous carbon has good electrical conductivity and can construct a conductive network at the material level to optimize the conductive properties of the material. By coating with amorphous carbon, the decomposition voltage of the lithium supplement material can be reduced, which helps to achieve effective replenishment of lithium ions at a lower voltage. Preferably, the thickness of the coating layer 2 ranges from 50 to 500 nm. For example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm and 500 nm. It will be appreciated by those skilled in the art that the thickness of the coating layer 2 can be set according to actual conditions. The coating layer 2 can protect the lithium supplement material to a certain extent, reduce side reactions with the electrolyte, and improve the structural stability of the material.
[0037] Preferably, the mass proportion of the lithium-supplementing material body 1 ranges from 80-99%, for example, 80%, 85%, 90%, 95%, and 99%. The mass proportion of the coating layer 2 ranges from 1-20%, for example, 1%, 5%, 10%, 15%, and 20%. The coating layer 2 represents a conductive carbon coating layer after heat treatment. By adjusting the mass proportion of the coating layer 2 and the lithium-supplementing material body 1, the thickness of the coating layer 2 can be precisely controlled, thereby optimizing the conductivity and electrochemical performance of the material.
[0038] In addition, if Figure 2 As shown, this embodiment also provides a method for preparing a positive electrode lithium-supplementing composite material. The preparation of the positive electrode lithium-supplementing composite material as described above specifically includes the following steps:
[0039] S1. Mixing the lithium supplement material and the carbon source to obtain a precursor;
[0040] S2. Heat-treating the precursor to obtain the positive electrode lithium-supplementing composite material.
[0041] In this embodiment, the carbon source includes one or more combinations of carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP) and glycerol. It will be appreciated by those skilled in the art that the carbon source can be selected according to actual needs, and may also include other carbon sources in addition to the present embodiment. The selected carbon source has a lower pyrolysis temperature, which can match the decomposition temperature of the lithium-supplementing material, thereby avoiding the problem of destroying the lithium-supplementing material due to high-temperature pyrolysis. In addition, these carbon sources can achieve in-situ carbon coating, that is, forming a uniform carbon layer on the surface of the lithium-supplementing material, which helps to improve the conductivity and electrochemical properties of the material. The coating of the amorphous carbon layer can significantly improve the conductivity of the lithium-supplementing material, thereby reducing the internal resistance during the charge and discharge process of the battery and improving the charge and discharge efficiency of the battery. The carbon layer can serve as a protective layer to reduce the side reactions between the lithium-supplementing material and the electrolyte, thereby extending the cycle life of the battery. The coating of the carbon layer helps to protect the structure of the lithium-supplementing material, reduce the volume expansion and contraction during the charge and discharge process, and improve the structural stability of the material.
[0042] In step S1 , more specifically, the lithium supplementing material and the carbon source are mixed to obtain a precursor composite; and the precursor composite is mixed uniformly to obtain a uniform precursor.
[0043] In this embodiment, the mixing of the lithium-replenishing material and the carbon source specifically includes: placing the lithium-replenishing material and the carbon source as solids into a container in a specified mass ratio, and adding a solvent to adjust the solid content to obtain the precursor composite. By mixing the lithium-replenishing material and the carbon source in a specified mass ratio, it is possible to ensure that both are evenly distributed in the precursor composite, which facilitates the subsequent carbon coating process. Adding a solvent to adjust the solid content can control the viscosity and solid-liquid ratio of the mixture, facilitating subsequent processing and treatment, such as kneading, ball milling, or drying. In addition, the mixing process helps to improve the dispersibility of the lithium-replenishing material and the carbon source in the solvent, reduce agglomeration, and improve the uniformity of the material.
[0044] As a preferred embodiment, the solvent component includes water and / or ethanol. It will be appreciated by those skilled in the art that the solvent can be selected according to actual needs and may also include other solvents in addition to those in this embodiment. This helps to reduce the impact on the environment during the preparation process. By using water or ethanol, the solid-liquid ratio of the mixture can be adjusted, thereby controlling the viscosity and fluidity of the mixture, facilitating subsequent process operations.
[0045] As a preferred embodiment, the solid content of the precursor compound ranges from 40% to 80%. For example, the solid content is 40%, 50%, 60%, 70% and 80%. The solid content within the range of 40-80% provides good adaptability for subsequent process steps such as drying and sintering, ensuring the stability of the material during processing. Appropriate solid content can adjust the fluidity of the mixture, facilitating the formation of a uniform coating or layer during mixing, kneading or coating. Appropriate adjustment of the solid content helps to control the evaporation rate of water during the drying process, avoiding excessively fast or excessively slow drying that leads to a decrease in material performance. Different solid contents can affect the porosity, density and mechanical strength of the final material, and these properties can be optimized by adjusting the solid content. Appropriate selection of solid content can reduce the amount of solvent used, thereby reducing the cost of raw materials.
[0046] In this embodiment, uniformly mixing the precursor composite comprises: uniformly mixing the precursor composite by a compounding method and drying the precursor composite at a predetermined temperature for a predetermined time. The compounding method ensures uniform distribution of the components in the precursor composite, avoids localized uneven concentrations, and thereby improves the performance consistency of the final product.
[0047] In step S2, the heat treatment of the precursor specifically includes: taking a predetermined mass of the precursor, placing it in a container, and sintering it in a specified gas atmosphere and a specified temperature for a specified time.
[0048] Thermal treatment facilitates chemical reactions and material migration among precursor components, forming the desired stable structure. Thermal treatment removes volatile and unstable components from the precursor, enhancing the chemical stability of the final product. Sintering under a defined atmosphere helps form a uniform amorphous carbon coating, improving the material's structural integrity and electrochemical activity.
[0049] In this embodiment, the specified gas atmosphere includes nitrogen, oxygen or argon. In view of the fact that the atmosphere is mainly used to construct an inert environment, they should not mix with each other, at least not with oxygen. It will be appreciated by those skilled in the art that, while achieving the same effect, the specified gas atmosphere can be set according to actual needs and may also include other gases in addition to the gases mentioned in this embodiment. Different gas atmospheres can provide different oxidation or reduction conditions, which help to form the desired material properties, such as improving the structural stability and chemical stability of the material.
[0050] In this embodiment, the designated temperature ranges from 100°C to 500°C. For example, the designated temperature may be 100°C, 200°C, 300°C, 400°C, and 500°C. Since lithium-supplementing materials are susceptible to decomposition at high temperatures, controlling the heat treatment temperature within the range of 100°C to 500°C can prevent material decomposition and maintain material integrity.
[0051] In this embodiment, the specified time ranges from 10 to 720 minutes (i.e., 10 minutes to 24 hours). The specified temperature can be 100°C, 200°C, 300°C, 400°C, and 500°C. Heat treatment within an appropriate temperature range can improve the thermal stability of the material and reduce performance degradation caused by temperature changes during battery use.
[0052] In addition, this embodiment also provides a lithium-ion battery, which is made of the positive electrode lithium-replenishing composite material as described above, or made of the positive electrode lithium-replenishing composite material made by the preparation method of the positive electrode lithium-replenishing composite material as described above.
[0053] In addition, this embodiment also provides a method for preparing a lithium-ion battery, using the positive electrode lithium-supplementing composite material as described above, or including the method for preparing the positive electrode lithium-supplementing composite material as described above, specifically comprising the following steps:
[0054] S100, mixing the active material with the positive electrode lithium-supplementing composite material to obtain a mixture;
[0055] S200, adjusting the viscosity and solid content of the mixture;
[0056] S300, coating the mixture on a conductive substrate to form a positive electrode sheet;
[0057] S400: Process the positive electrode sheet and the negative electrode sheet to obtain a battery.
[0058] In this embodiment, the active material includes lithium iron phosphate (LFP). The positive electrode lithium-supplementing composite material can improve the initial coulombic efficiency and capacity of the battery, thereby increasing the energy density of the battery.
[0059] In step S300, the mixture is evenly coated on the conductive substrate, specifically comprising: evenly coating the mixture on both sides of the conductive substrate and drying. The mixture evenly coated on the conductive substrate can ensure uniform reaction of the electrode material during the charge and discharge process.
[0060] In step S400, the positive and negative electrode sheets are processed, specifically including at least one of rolling, die-cutting, slitting, assembling, baking, and injecting the positive and negative electrode sheets. Uniform coating and drying processes can improve the utilization rate of active materials and reduce material waste. These rolling, die-cutting, slitting, assembling, and baking processes help form a stable electrode structure and enhance the mechanical strength of the battery.
[0061] As a preferred embodiment, the composite method of the lithium-supplementing material 1 and the coating layer 2 includes one or a combination of dry kneading, ball milling, or hydrothermal processing. Those skilled in the art will appreciate that other composite methods can be used to achieve the same effect. However, in this embodiment, the composite methods of the lithium-supplementing material 1 and the coating layer 2 are exemplified by dry kneading, ball milling, and hydrothermal processing.
[0062] Example 1
[0063] Precursor synthesis: CMC and lithium oxalate are put into a stirring tank in a mass ratio of 1:4, water is added to adjust the solid content to 60%, and the mixture is mixed by revolution kneading for 1 hour (i.e., stirring kneading or dry kneading), and dried at 80°C for 2 hours to obtain precursor powder (i.e., precursor) to be processed.
[0064] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 350° C. for 30 min under a nitrogen atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for later use.
[0065] Lithium supplement battery assembly: add active materials (e.g., LFP (lithium iron phosphate): SP (conductive carbon black, i.e., a conductive agent): PVDF (polyvinylidene fluoride, i.e., a binder): composite lithium supplement additive = 85:5:5:5) in a mass ratio and stir to mix, adjust the viscosity and solid content with NMP (i.e., use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry), evenly coat on both sides of aluminum foil (i.e., a conductive substrate), and dry to obtain a lithium supplemented positive electrode sheet with an area density of, for example, 16.8 mg / cm 2 ; The above-mentioned positive electrode sheets and conventional negative electrode sheets are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form batteries (such as soft-pack batteries, i.e., lithium-ion batteries in this embodiment), and the relevant performance is tested.
[0066] The first charge and discharge performance test: the battery was placed at 45 ° C for 10 hours, 0.1C constant current charge ("C" represents the rated capacity of the battery, 0.1C means 10% of the rated capacity of the battery as the charging current) to 3.65V, 0.01C constant current charge to 4.3V, 0.1C constant current discharge to 2.5V, and then 25 ° C 0.5C charge and discharge cycle.
[0067] Example 2
[0068] Compared with Example 1, the differences are: CMC is replaced by glycerol; the compounding method is changed from stirring and kneading to wet ball milling (ie, ball milling); the solid content is 30%; and the precursor is sintered at 400° C. for 8 h in an argon atmosphere.
[0069] More specifically, precursor synthesis: propylene glycol and lithium oxalate are put into a stirring tank in a mass ratio of 1:4, water is added to adjust the solid content to 30%, wet ball milling is performed for 1 hour until the mixture is evenly mixed, and drying is performed at 80°C for 2 hours to obtain a precursor powder (i.e., precursor) to be processed.
[0070] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 400° C. for 8 h under an argon atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for standby use.
[0071] Lithium supplement battery assembly: add active materials according to the mass ratio (for example, LFP (lithium iron phosphate): SP (conductive carbon black): PVDF (polyvinylidene fluoride): composite lithium supplement additive = 85:5:5:5) and stir to mix. Adjust the viscosity and solid content with NMP, that is, use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry. Evenly coat it on both sides of aluminum foil (i.e., conductive substrate) and dry it to obtain the positive electrode sheet after lithium supplementation. The surface density is, for example, 16.8 mg / cm 2; The above-mentioned positive electrode sheet and the conventional negative electrode sheet are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form a battery, such as a soft-pack battery, that is, the lithium-ion battery in this embodiment, and the relevant performance is tested.
[0072] Initial charge and discharge performance test: The battery was placed at 45°C for 10 hours at 0.1C (where "C" represents the rated capacity and 0.1C means 10% of the rated capacity). Constant current charging was performed to 3.65V, followed by 0.01C constant current charging to 4.3V, and then 0.1C constant current discharge to 2.5V. The battery was then cycled at 25°C and 0.5C.
[0073] Example 3
[0074] Compared with Example 1, the differences are: CMC is replaced by PVP; PVP: lithium oxalate are added at a mass ratio of 1:1; the compounding method is changed from stirring and kneading to a hydrothermal method, with a solid content of 50%; and sintering is performed under an oxygen atmosphere.
[0075] More specifically, precursor synthesis: PVP and lithium oxalate are put into a stirring tank in a mass ratio of 1:1, water is added to adjust the solid content to 50%, hydrothermal method is used for 1 hour until the mixture is uniformly mixed, and drying is carried out at 80°C for 2 hours to obtain precursor powder (i.e., precursor) to be processed.
[0076] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 350° C. for 30 min under an oxygen atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for later use.
[0077] Lithium supplement battery assembly: add active materials according to the mass ratio (for example, LFP (lithium iron phosphate): SP (conductive carbon black): PVDF (polyvinylidene fluoride): composite lithium supplement additive = 85:5:5:5) and stir to mix. Adjust the viscosity and solid content with NMP, that is, use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry. Evenly coat it on both sides of aluminum foil (i.e., conductive substrate) and dry it to obtain the positive electrode sheet after lithium supplementation. The surface density is, for example, 16.8 mg / cm 2 ; The above-mentioned positive electrode sheet and the conventional negative electrode sheet are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form a battery, such as a soft-pack battery, that is, the lithium-ion battery in this embodiment, and the relevant performance is tested.
[0078] Initial charge and discharge performance test: The battery was placed at 45°C for 10 hours at 0.1C (where "C" represents the rated capacity and 0.1C means 10% of the rated capacity). Constant current charging was performed to 3.65V, followed by 0.01C constant current charging to 4.3V, and then 0.1C constant current discharge to 2.5V. The battery was then cycled at 25°C and 0.5C.
[0079] Example 4
[0080] Compared with Example 1, the differences are: lithium oxalate is changed to lithium peroxide; LFP:SP:PVDF:composite lithium supplement additive=80:5:5:10.
[0081] Precursor synthesis: CMC and lithium peroxide are put into a stirring tank in a mass ratio of 1:4, water is added to adjust the solid content to 60%, and the mixture is mixed evenly by orbital kneading for 1 hour (i.e., stirring kneading or dry kneading), and dried at 80°C for 2 hours to obtain precursor powder (i.e., precursor) to be processed.
[0082] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 350° C. for 30 min under a nitrogen atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for later use.
[0083] Lithium supplement battery assembly: add active materials according to the mass ratio (for example, LFP (lithium iron phosphate): SP (conductive carbon black): PVDF (polyvinylidene fluoride): composite lithium supplement additive = 80:5:5:10) and stir to mix. Adjust the viscosity and solid content with NMP, that is, use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry. Evenly coat it on both sides of aluminum foil (i.e., conductive substrate) and dry it to obtain the positive electrode sheet after lithium supplementation. The surface density is, for example, 16.8 mg / cm 2 ; The above-mentioned positive electrode sheet and the conventional negative electrode sheet are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form a battery, such as a soft-pack battery, that is, the lithium-ion battery in this embodiment, and the relevant performance is tested.
[0084] Initial charge and discharge performance test: The battery was placed at 45°C for 10 hours at 0.1C (where "C" represents the rated capacity and 0.1C means 10% of the rated capacity). Constant current charging was performed to 3.65V, followed by 0.01C constant current charging to 4.3V, and then 0.1C constant current discharge to 2.5V. The battery was then cycled at 25°C and 0.5C.
[0085] Reference example 1
[0086] Compared with Example 1, the differences are: precursor synthesis: none; sintered carbon coating: none; battery assembly: various active materials (LFP: SP: PVDF: lithium oxalate = 85:5:5:5).
[0087] Precursor synthesis: CMC and lithium oxalate are put into a stirring tank in a mass ratio of 1:4, water is added to adjust the solid content to 60%, and the mixture is mixed by revolution kneading for 1 hour (i.e., stirring kneading or dry kneading), and dried at 80°C for 2 hours to obtain precursor powder (i.e., precursor) to be processed.
[0088] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 350° C. for 30 min under a nitrogen atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for later use.
[0089] Lithium-supplemented battery assembly: Add each active material (LFP:SP:PVDF:lithium oxalate=85:5:5:5) according to the mass ratio and stir to mix. Adjust the viscosity and solid content with NMP, that is, use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry. Evenly coat it on both sides of aluminum foil (i.e., conductive substrate) and dry it to obtain the lithium-supplemented positive electrode sheet, with an area density of 16.8 mg / cm 2 ; The above-mentioned positive electrode sheet and the conventional negative electrode sheet are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form a battery, such as a soft-pack battery, that is, the lithium-ion battery in this embodiment, and the relevant performance is tested.
[0090] Initial charge and discharge performance test: The battery was placed at 45°C for 10 hours at 0.1C (where "C" represents the rated capacity and 0.1C means 10% of the rated capacity). Constant current charging was performed to 3.65V, followed by 0.01C constant current charging to 4.3V, and then 0.1C constant current discharge to 2.5V. The battery was then cycled at 25°C and 0.5C.
[0091] Reference example 2
[0092] Compared with Example 1, the differences are: sintered carbon coating: sintering at 800° C. for 8 h; battery assembly: active materials (LFP: SP: PVDF: lithium oxalate = 85:5:5:5).
[0093] Precursor synthesis: CMC and lithium oxalate are put into a stirring tank in a mass ratio of 1:4, water is added to adjust the solid content to 60%, and the mixture is mixed by revolution kneading for 1 hour (i.e., stirring kneading or dry kneading), and dried at 80°C for 2 hours to obtain precursor powder (i.e., precursor) to be processed.
[0094] Sintered carbon coating: 10 g of the precursor powder was placed in a tube furnace and sintered at 800° C. for 8 h under a nitrogen atmosphere to obtain a composite lithium replenishing additive (i.e., a positive electrode lithium replenishing composite material) for standby use.
[0095] Lithium-supplemented battery assembly: Add each active material (LFP:SP:PVDF:lithium oxalate=85:5:5:5) according to the mass ratio and stir to mix. Adjust the viscosity and solid content with NMP, that is, use N-methylpyrrolidone to adjust the viscosity and solid content of the electrode slurry. Evenly coat it on both sides of aluminum foil (i.e., conductive substrate) and dry it to obtain the lithium-supplemented positive electrode sheet, with an area density of 16.8 mg / cm 2; The above-mentioned positive electrode sheet and the conventional negative electrode sheet are subjected to processes such as sheet rolling, die-cutting, striping, assembly, baking, and liquid injection to form a battery, such as a soft-pack battery, that is, the lithium-ion battery in this embodiment, and the relevant performance is tested.
[0096] Initial charge and discharge performance test: The battery was placed at 45°C for 10 hours at 0.1C (where "C" represents the rated capacity and 0.1C means 10% of the rated capacity). Constant current charging was performed to 3.65V, followed by 0.01C constant current charging to 4.3V, and then 0.1C constant current discharge to 2.5V. The battery was then cycled at 25°C and 0.5C.
[0097] According to Example 1, Example 2, Example 3, Example 4, Reference Example 1 and Reference Example 2, the data in Table 1 are obtained, as shown in the following table:
[0098] Group First charge capacity (Ah) 1000 cycles capacity retention rate Example 1 2.10 90.1% Example 2 2.17 90.8% Example 3 2.20 90.4% Example 4 2.46 91.5% Reference example 1 1.98 88.0% Reference example 2 1.95 87.6%
[0099] According to the data in Table 1 above, the following conclusions can be drawn: Comparing Examples 1-4 with Reference Example 1, the first charging capacity of each group of the examples is significantly higher than that of Reference Example 1, indicating that this treatment method (i.e., the method of each embodiment) has an improvement effect on the capacity of the lithium supplement agent. Comparing Example 1 with Reference Examples 1-2, it is shown that the carbon source and the main lithium supplement material have a certain operating temperature range. At high temperatures, the carbon source can also be pyrolyzed and carbonized, but this temperature has a certain effect on the stability of the main lithium supplement material, and it is unable to exert the lithium supplement effect. Comparing Example 1 with Example 2, the first charging capacity of Example 2 increases, indicating that the carbon coating sintering conditions affect the capacity of the composite lithium supplement additive. Comparing Example 1 with Example 3, the first charging capacity of Example 3 increases, indicating that the effects of different carbon sources after sintering are different, and adjusting the carbon coating ratio after sintering affects the capacity of the composite lithium supplement additive. Comparing Example 1 with Example 4, it is shown that changing the amount of composite lithium supplement additive added affects the subsequent battery performance. For example, Figure 3 The experimental diagram obtained in Example 1 and Figure 4 The experimental figure obtained from reference example 1 is shown in FIG.
[0100] In summary, the positive electrode lithium-supplementing composite material, lithium-ion battery and preparation method thereof proposed in the present invention have the following advantages:
[0101] The positive-electrode lithium-replenishing composite material produced by this method not only increases conductivity and reduces decomposition voltage compared to existing lithium-replenishing additives and relatively pure lithium-replenishing additives, but also increases lithium-replenishing capacity. Furthermore, the positive-electrode lithium-replenishing composite material produced by this method has a lower proportion of conductive carbon and is physically blended, resulting in improved conductivity optimization. Furthermore, this method does not involve decomposing the carbon source at high temperatures, avoiding the problem of material temperature mismatch, thereby enabling in-situ surface carbon coating of the main lithium-replenishing material at lower temperatures.
[0102] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A positive electrode lithium supplement composite material, characterized in that: It comprises a lithium supplement material body and a coating layer; the coating layer covers the surface of the lithium supplement material body.
2. The positive electrode lithium supplement composite material according to claim 1, characterized in that The lithium-supplementing material in the lithium-supplementing material body includes one or more combinations of lithium peroxide, lithium oxalate, and lithium carbonate.
3. The positive electrode lithium supplement composite material according to claim 1, characterized in that The particle size of the main body of the lithium supplement material ranges from 0.5 to 10 μm; the main component of the coating layer includes amorphous carbon; the thickness of the coating layer ranges from 50 to 500 nm; the mass proportion of the main body of the lithium supplement material ranges from 80 to 99%, and the mass proportion of the coating layer ranges from 1 to 20%.
4. A method for preparing a positive electrode lithium-supplementing composite material, comprising preparing the positive electrode lithium-supplementing composite material according to any one of claims 1 to 3, characterized in that: The details include: mixing the lithium supplement material with a carbon source to obtain a precursor; The precursor is subjected to heat treatment to obtain the positive electrode lithium supplement composite material.
5. The method for preparing the positive electrode lithium supplement composite material according to claim 4, wherein: The carbon source includes one or more combinations of carboxymethyl cellulose, polyvinyl pyrrolidone and glycerol.
6. The method for preparing the positive electrode lithium supplement composite material according to claim 5, wherein: The lithium-supplementing material and the carbon source are mixed to obtain a precursor, which specifically includes: adding the lithium-supplementing material and the carbon source into a container according to a specified mass ratio, adding a solvent to adjust the solid content, mixing evenly and drying to obtain the precursor.
7. The method for preparing the positive electrode lithium supplement composite material according to claim 6, wherein: The solvent component includes water and / or ethanol; the solid content ranges from 40% to 80%.
8. The method for preparing the positive electrode lithium supplement composite material according to claim 6, wherein: The heat treatment of the precursor specifically includes: taking the precursor, placing it in a container, and sintering it in a specified gas atmosphere and a specified temperature for a specified time.
9. The method for preparing the positive electrode lithium supplement composite material according to claim 8, wherein: The designated gas atmosphere includes nitrogen, oxygen or argon; the designated temperature ranges from 100-500° C.; and the designated time ranges from 10-720 min.
10. A lithium ion battery, characterized in that: The positive electrode lithium-replenishing composite material is made from the positive electrode lithium-replenishing composite material according to any one of claims 1 to 3, or is made from the positive electrode lithium-replenishing composite material prepared by the preparation method of the positive electrode lithium-replenishing composite material according to any one of claims 4 to 9.
11. A method for preparing a lithium-ion battery, using the positive electrode lithium-supplementing composite material according to any one of claims 1 to 3, or comprising the method for preparing the positive electrode lithium-supplementing composite material according to any one of claims 4 to 9, characterized in that: The details include: mixing the active material with the positive electrode lithium-supplementing composite material to obtain a mixture; adjusting the viscosity and solid content of the mixture; coating the mixture on a conductive substrate to form a positive electrode sheet; The positive electrode sheet and the negative electrode sheet are processed to obtain a battery.
12. The method for preparing a lithium-ion battery according to claim 11, wherein: The active material includes lithium iron phosphate.